Droplet evaporation on a solid surface exposed to forced convection: Experiments, simulation and dimensional analysis. (October 2017) - Doursat, Christophe; Lecoq, Logan; Laguerre, Onrawee; Flick, Denis
Highlights: Droplet geometry changes modeling during pinning and unpinning periods. Coupled heat and mass transfer taken into account. Good agreement with experiments with stainless steel and PVC plates. Charts based on dimensional analysis allow estimating drying time in various conditions. Abstract: Experiments were carried out in order to study the evolution of the mass and wetted surface during evaporation of pure water droplets on stainless steel and PVC plates exposed to forced air convection. The numerical model developed takes into account both coupled heat and mass transfer phenomena and the change in droplet geometry during both pinning and receding periods. The comparison between experimental results and simulation shows good agreement. The model is able to reproduce the influence of the plate properties and that of relative humidity. Dimensional analysis was performed and dimensionless diagrams were developed to predict the drying time for water droplets on stainless steel under a broad range of operating conditions.